Firewood and Carpentry Wood Contribution to the Communities of Mutis Timau Protected Forest, Timor Island - Fransiskus Xaverius Dako; Ris Hadi Purwanto; Lies Rahayu Wijayanti Faida; Sumardi Sumardi (Institut Pertanian Bogor (IPB University), 2018)
The existence of Mutis Timau Protected Forest (MTPF) has given a real contribution to the community by providing household energy needs and raw materials for building the houses. This preliminary study is aimed at knowing the contribution of M T PF in terms of firewood and carpentry wood consumption in the community. The study was conducted in 9 villages located in and around MTPF. This study used surveys and employed descriptive analysis with 353 families spread proportionally on every village as the sample. The results show that MTPF contributed to as much as 87.45% of the total firewood consumption of the community living in and around the protected forest, while the remaining 12.55% was supplied from the gardens. These percentages were calculated from the total firewood consumption of 1,912,512 kg year-1. Meanwhile, every 15-20 years, MTPF contributed to 96.98% of the total carpentry wood needs (1,177.3 m3) while the remaining 3.02% was supplied from privately owned gardens. This fact indicates that the dependence level of the community on the forest is high. Consequently, the pressure on the forest is also very high and may cause deforestation and degradation. To prevent deforestation and degradation, social participation in the sustainable management of MTPF is needed. The principles of social forestry must be implemented through social forestry programs such as community empowerment.